Study on the Effects of Carbon Fibers and Carbon nanofibers on Electrical Conductivity of Concrete. Issue 3 (May 2019) - Wang, Tengjiao; Xu, Jinyu; Bai, Erlei; Luo, Xin; Chen, Haowen; Liu, Gaojie; Chang, Sen
Abstract: In order to study the effects of carbon fibers and carbon nanofibers on the electrical conductivity of concrete, we adopt the four-electrode method to measure the resistivity of concrete with different test voltages, different ages and different fiber content. The test results show that both carbon fibers and carbon nanofibers can significantly reduce the electrical resistivity of concrete. When carbon fiber content and carbon nanofiber content are same, the resistivity of carbon fiber reinforced concrete (CFRC) is lower than that of carbon nanofiber reinforced concrete (CNFRC). The resistivity of CFRC and CNFRC can decrease with the increase of the test voltage, increase with the development of the concrete, and decrease with the increase of the fiber content. For concrete with an age of 28 days, CFRC has the largest decrease in resistivity when the carbon fiber content is between 0.2% and 0.3%, and the resistivity of CNFRC drops biggest when the carbon nanofiber content is between 0.1% and 0.3%.